Germany's labor market problems: What to do and what not to do? A survey among experts - Stefan Profit; Rolf Tschernig (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
In this study we collect information on what economists would suggest for reducing German unemployment. This was done by conducting a detailed survey containing 35 measures at two conferences of different kind. One conference was a small conference at the Humboldt-University in Berlin attended by leading researchers on the German labor market, the other the 1998 Meeting of the European Economic Association. We statistically identify a set of measures that is viewed superior to the remaining ones independently of the survey chosen. In a similar way, the responses allow to identify a set of measures that should be avoided. These lists were obtained by recursively applying the Friedman test which is based on individual rankings of survey participants. While the former set of measures contains a selective group of institutional reforms and supply-side policies, the latter is dominated by demand-management policies.
urn:nbn:de:kobv:11-10060654
Keywords: C42; E61; J21; 330